System for Digital 1D-Image Processing with 1024 Pixel CCD Sensor - Kulla, P.; Sevcik, P.; Chrenek, M.; Misun, J. (Radioengineering Society, 1993)
The conception of system for digital 1D-images processing with digital CCD camera is presented. The system is created from these three basic parts: the digital CCD camera with linear image sensor CCD L133C, 8-bit interface and a personal computer. The scanning digital CCD camera generated a video signals, which are processed in the analog signal processor. The output signal is continually converted to 8-bit data words in A/D converter. This data words maybe transfer over a bus driver to the operation memory of personal computer, by setting one of the three work regimes of digital CCD camera. Some application possibilities and basic technical parameters of this system are given.
Keywords: linear CCD sensor; digital CCD camera; signal processor; interface; digital 1D-image processing